Magnetohydrodynamic convection effects with viscous and ohmic dissipation in a vertical channel partially filled by a porous medium. - Chauhan, Dileep Singh (Journal of Applied Science and Engineering)
The fully developed MHD mixed convection flow in a vertical channel, partially filled with clear fluid and partially filled with a fluid-saturated porous medium, is investigated by taking into account viscous and Ohmic dissipations. The bounding impermeable walls of the channel are maintained at different constant temperatures. The isothermal-isoflux and isoflux-isothermal temperature conditions on the walls have also been considered. The flow in the porous medium is modeled by the Brinkman equation and the Boussinesq approximation holds. The velocity and temperature distributions in the composite channel are obtained numerically by shooting technique with fourth order Runge-Kutta method and analytically by perturbation series method. These results have been depicted graphically, compared and discussed.